The applications of social commerce constructs - Shanmugam M.; Sun S.; Amidi A.; Khani F.; Khani F. (Elsevier Ltd, 2023)
Online systems; Social networking (online); Emotional supports; Informational support; On-line communities; Quantitative study; Social commerces; Structural equation modeling; Theoretical foundations; Trust; Commerce